2020
DOI: 10.1021/acs.jpcc.0c03255
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Density Functional Theory Study of Cinchonidine and Hydrogen Coadsorption on Platinum Group Metals (Rh, Ir, Pd, and Pt) and Its Implications on Surface Chiral Site Formation

Abstract: Coadsorption of hydrogen and cinchonidine (CD), the chiral modifier most frequently applied to bestow chiral sites onto platinum group metals, has been studied theoretically. In focus was the stability and configuration (spatial orientation) of CD adsorbed on the (111) surfaces of Rh, Ir, Pd, and Pt. On all these metals, CD is shown to be adsorbed with the quinoline moiety laying nearly parallel to the surface, likely through πbonding. At high H-coverages, the position of the quinoline ring becomes tilted and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…It should be noted that exposure to reaction conditions involves the addition of various factors that can also affect the adsorption geometry of the ligands and their interaction with the prochiral reactant. It was demonstrated that the surface adsorption of hydrogen, , solvent molecules, , coadsorption of modifiers, , and reactants can alter the reaction mechanism and the adsorption geometry of surface ligands. It cannot be excluded that similar factors will also modify the adsorption geometry of NHC ligands during the enantioselective α-arylation reaction.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that exposure to reaction conditions involves the addition of various factors that can also affect the adsorption geometry of the ligands and their interaction with the prochiral reactant. It was demonstrated that the surface adsorption of hydrogen, , solvent molecules, , coadsorption of modifiers, , and reactants can alter the reaction mechanism and the adsorption geometry of surface ligands. It cannot be excluded that similar factors will also modify the adsorption geometry of NHC ligands during the enantioselective α-arylation reaction.…”
Section: Resultsmentioning
confidence: 99%
“…However, it was shown that in aprotic solvents and the gas-phase, the proton can also be delivered by the Pt-surface (as a spill-over, one might say), 89,90 although Hahn and Baiker described the process consistently as H atom transfer. 91 Mechanistically, the chemistry of these modifying chiral ligands on the surface could be closely related to heterolytic cleavage. However, in the vast literature on ligand-induced, heterogeneous, asymmetric hydrogenations, heterolytic cleavage does not seem to play a role in the discussions and we mention this catalysis only here in the introduction.…”
Section: Enantioselective Hydrogenationmentioning
confidence: 99%
“…The adsorption of quinolines and derivatives thereof on metals and metal oxides plays an important role in many fields, including heterogeneous catalysis, environmental pollution, and corrosion inhibitors . Spectroscopic investigations and density functional theory (DFT) studies have shed some light on the adsorption modes and energetics of quinolines on platinum group (PG) metals. Particularly, substantial experimental work has been expended to examine the adsorption of cinchona alkaloids, derivatives of quinoline, which are applied to impart chirality to PG metal catalysts for the enantioselective hydrogenation of activated ketones. A comprehensive and critical review of adsorption studies of various aromatic and N-heteroaromatic compounds on metals by first-principles DFT published till 2009 has been provided by Jenkins .…”
Section: Introductionmentioning
confidence: 99%